Relationship between Plasma Cell Density and Clinico-histopathological Characteristics of DLBCL - Nyimas Chodijah; Krisna Murti; Riana Sari Puspita Rasyid (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Diffuse Large B Cell Lymphoma (DLBCL) is a malignancy derived from the malignant transformation of B cells from the germinal center. This type of non-Hodgkin's lymphoma is the most common and represents about 30-40% of all cases. The tumor microenvironment of B-cell lymphoma plays an important role in the regulation of tumor cell survival and proliferation. Plasma cells in the tumor microenvironment have an important role in the formation of the anti-tumor immune response, even in low numbers, these cells can produce large amounts of cytokines and antibodies. The purpose of this study was to determine the relationship between plasma cell density and clinico-histopathological characteristics of DLBCL patients. A cross-sectional study was conducted. The samples of this study were paraffin blocks of DLBCL patients referred to Anatomic Pathology Departement Faculty of Medicine Universitas Sriwijaya/RSUP Dr. Mohammad Hoesin Palembang. From 50 cases during the 2018-2020 period, 32 samples were selected. Plasma cells were morphologically identified on HE slides. Statistical analysis was performed using the chi-square test. The distribution of DLBCL cases found more in the age group <60 years (56,3%), male gender (68,8%), extranodal tumor location (56,3%). Centroblastic variants were higher (78,1%) than others, and the non-GCB subtype (78,1%) was higher than the GCB. There is no significant relationship between plasma cell density and the clinico-histopathological characteristics of DLBCL age, sex, tumor location, variant, and subtype.